LANGUAGE IMPOLITENESS IN JAKARTA LAWYERS CLUB TALK SHOW 2014 - Meisa Fitri Nasution (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2017)
The objectives of this descriptive qualitative study were to discover: (1) the types of impoliteness strategy, (2) types of attacks, and (3) how the responses to the impolite attack in Jakarta Lawyers Club (JLC) Talk Show on TVOne. The source of data were the participants’ utterances in JLC Talk Show from the topics of Talk Show namely Badai Demokrat Menerjang Kemana–Mana, Anas Siap Digantungdi Monas, and Dibalik Bungkamnya Nazaruddin in order to find out therecurrences and the pattern of the data based on the problem of the study. The data were identified, analyzed and categorized based on Culpeper’s (1996) theory. The findings of the study shows that: 1) there were four types of impoliteness strategies appeared in JLC Talk Show, namely Bald On Record Impoliteness (37.5%), Positive Impoliteness (27.5%), Negative Impoliteness (25.0%), and Sarcasm (10%), 2) there were two types of attacks appeared in JLC Talk Show namely Attacks on Quality Face (92.5%) and Attacks on Social Identity Face (7.5%), and 3) in responding to the impolite attacks, there were three ways appeared in JLC Talk Show namely not responding (52.5%), countering defensively (32.5%), and countering offensively (15.0%). The findings shows that JLC Talk Show was a formal context of Talk Show in which its participants were educated people who mostly use a direct strategy of impoliteness (Bald On Record Impoliteness) in attacking on the other participants’ personal quality (Quality Face) but the attacks dominantly were not responded by them. Therefore, it can be concluded that in communication, everyone may convey his or her opinions, arguments, and feelings but he or she should express the good attitude to communicate. Some suggestions are directed to those who are interested in understanding impoliteness strategy as found in practice.